IMPLEMENTASI MEDIA “BARNETO” MELALUI METODE “DORA” UNTUK MENINGKATKAN KETERAMPILAN BERCERITA NARRATIVE BAHASA INGGRIS SISWA KELAS IX-E SMP NEGERI 4 TUBAN - Lilik Dyah Wulandari; Saliman Saliman (Jurnal Didaktika Pendidikan Dasar, 2019)
The activeness of inter-student English-language communication in class is still very lacking. Students tend to be passive and lack of confidence in communicating using English. Student’s ability in telling stories is still unsatisfactory. This research is intended to find alternative solutions to improve their abilities in narrative stories. "Barneto Dora" is offered as a method to overcome those problems. The purpose of this study is to describe the application of Barneto Dora and to find out the results of its improvements. The method used in this study is classroom action research. The research subjects are students of Class IX E of SMP 4 Tuban. The technique of collecting data used in this study are observation, field notes, questionnaires, and tests. The data is analyzed by qualitative and quantitative data analysis techniques. The results indicate that through Barneto Dora, students' English storytelling skills increased significantly. This increase can be seen from the increase in the average class score in storytelling. The previous class average score is 55.27 and increased to 78.00.